Pengaruh Brand Image, Product Quality dan Presepsi Harga Terhadap Minat Beli Iphone di Cilacap - Ade Prasetyo Nugroho; Nur Khasanah (SMARTINDO, 2025)
This study aims to test and determine the effect of Brand Image, Product Quality and Price Perception on Interest in Buying an Iphone in Cilacap Regency. This research was conducted on the people of Cilacap Regency who use an Iphone. Data collection was carried out through distributing questionnaires to 100 respondents. This study uses analytical techniques, namely descriptive and statistical analysis including validity tests, reliability tests, classical assumption tests, hypothesis testing and multiple regression analysis. Software technique used is using SPSS version 25 for windows. The hypothesis results obtained show that partially and Simultaneously Brand Image, Product Quality, and Price Perception have an effect on Purchase Intention.